ANALISIS KELEMBAGAAN SKEMA IZIN PEMANFAATAN HUTAN PERHUTANAN SOSIAL PADA KAWASAN HUTAN LINDUNG GUNUNG RAKUTAK JAWA BARAT - Almaghfiroh, Choiruriwayancanti Fatimah; Pujo, Pujo; -, Mulyaningrum (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
In developing a sustainable Social Forestry system in Indonesia, it is necessary to strengthen institutional and appropriate administrative management. This research aims to identify the characteristics of the institutional aspects of the Social Forestry Forest Utilization Permits (SFFUP) scheme in Mount Rakutak protection forest area. This research was conducted using criteria and indicator assessment methods that refer to sustainable social forestry institutional management. Data collection was carried out using a closed interview method with SFFUP participants. The results of research on institutional characteristics show that the policy implementation aspect is in the good category, the leadership aspect is in the good category, the institutional management aspect is in the bad category, the group transparency aspect is in the bad category, the aspect of trust towards stakeholders is in the good category, the conflict management aspect is in the fair category and the member development aspect is in the bad category. The results of the overall assessment of institutional aspects show that the implementation of the SFFUP scheme has not paid attention to sustainable governance of institutional aspects. To realize the successful implementation of SFFUP scheme, it is necessary to strengthen institutional aspects based on the 7 criteria and 30 indicators that have been found in this research.